Effects of Noninvasive Brain Stimulation Combined With Antidepressants in Patients With Poststroke Depression: A Systematic Review and Meta-Analysis - Liang, Jiabin; Feng, Jie; He, Jinhua; Jiang, Yong; Zhang, Haoyu; Chen, Hanwei (Frontiers in Pharmacology, 2022)
Objective: To evaluated the efficacy and safety of NIBS combined with antidepressants in patients with PSD. Methods: Seven databases were searched (October 31, 2021) to identify randomized controlled trials of NIBS combined with antidepressants in the treatment of PSD according to the inclusion and exclusion criteria. Two researchers independently screened the identified studies, extracted their characteristics, and evaluated the quality of the included literature. Cochrane Collaboration’s tool was used to assess risk of bias. RevMan 5.3 software was applied for meta-analysis. Results: A total of 34 randomized controlled trials that combined NIBS with antidepressant therapy were included, involving 2,711 patients with PSD. Meta-analysis showed that the total effective rate was higher in the NIBS combined with antidepressant group than in the antidepressant alone group [odds ratio (OR): 4.33; 95% confidence interval (CI): 3.07 to 6.11; P<0.00001]. The Hamilton depressive scale (HAMD) score was significantly lower in the group comprising repeated transcranial magnetic stimulation (rTMS) with a frequency less than 10 Hz combined with fluoxetine or paroxetine hydrochloride than in the antidepressant alone group [standard mean difference (SMD): −1.44; 95% CI: −1.86 to −1.03; P<0.00001]. No significant difference was seen with rTMS with a frequency exceeding 10 Hz combined with fluoxetine versus fluoxetine alone (SMD: −4.02; 95% CI: −10.43 to 2.39; P=0.22). In addition, combination therapy more strongly improved the modified Barthel index scale than antidepressants [mean difference (MD): 8.29; 95% CI: 5.23–11.35; P<0.00001]. Adverse effects were not significantly different between the NIBS combined with antidepressant group and the antidepressant group (OR: 1.33; 95% CI: 0.87 to 2.04; P=0.18). Discussion: Low-frequency rTMS combined with fluoxetine or paroxetine hydrochloride is more effective than antidepressants alone in patients with PSD, and there are no significant adverse effects. The same results were found for combined transcranial electrical stimulation and antidepressants. In addition, combined therapy may enhance quality of life after stroke.